Assistance in the Implementation of Management Control Systems in Sago-Based Café MSMEs Through SWOT Analysis to Improve Business Sustainability in Jayapura City - Maylen K. P. Kambuaya; Pascalina V.S Sesa; Gian Giovania; Inverny S. Pattiruhu (International Journal Of Community Service, 2026)
Many MSMEs have not implemented adequate managerial and accounting practices, especially in management control and inventory management, making them vulnerable to cost waste, stock loss, and disruption of business continuity that threatens long-term business sustainability. A review study on management accounting practices in MSMEs confirms the important role of these practices in improving operational efficiency and managerial decision-making capabilities. The implementation of a simple and scalable Management Control System (SPM) can help MSMEs standardize processes, separate key tasks, and provide information for control and decision-making. SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis provides a simple yet powerful framework to evaluate the internal and external conditions of MSMEs before designing or adjusting SPM and inventory policies. By incorporating SWOT findings into management control design—for example, by leveraging internal strengths to implement simple record-keeping, addressing weaknesses through staff training, exploiting local market opportunities, and anticipating supply chain threats—MSMEs can design more adaptive and sustainable strategies. Through mentoring activities, Sasagu Cafe MSMEs gain an understanding of the importance of implementing a management control system that includes business planning, inventory control, financial management, division of tasks and responsibilities, and evaluation of the business environment through SWOT analysis. The results of the analysis show that this business has a great opportunity to grow if it is able to take advantage of its strengths and overcome various weaknesses that still exist.